VALIDATION OF THE LAND WATER STORAGE FROM GRAVITY RECOVERY AND CLIMATE EXPERIMENT (GRACE) WITH GAUGE DATA IN THE AMAZON BASIN - COSTA, SONIA MARIA ALVES; DE MATOS, ANA CRISTINA OLIVEIRA CANCORO; BLITZKOW, DENIZAR (Boletim de Ciências Geodésicas, 2012)
The Amazon basin is a region of constant scientific interest due to its environmental importance and its biodiversity and climate on a global scale. The seasonal variations in water volume are one of the examples of topics studied nowadays. In general, the variations in river levels depend primarily on the climate and physics characteristics of the corresponding basins. The main factor which influences the water level in the Amazon Basin is the intensive rainfall over this region as a consequence of the humidity of the tropical climate. Unfortunately, the Amazon basin is an area with lack of water level information due to difficulties in access for local operations. The purpose of this study is to compare and evaluate the Equivalent Water Height (Ewh) from GRACE (Gravity Recovery And Climate Experiment) mission, to study the connection between water loading and vertical variations of the crust due to the hydrologic. In order to achieve this goal, the Ewh is compared with in-situ information from limnimeter. For the analysis it was computed the correlation coefficients, phase and amplitude of GRACE Ewh solutions and in-situ data, as well as the timing of periods of drought in different parts of the basin. The results indicated that vertical variations of the lithosphere due to water mass loading could reach 7 to 5 cm per year, in the sedimentary and flooded areas of the region, where water level variations can reach 10 to 8 m.